Molecular Subtyping of Human Rhinovirus in Children from Three Sub-Saharan African Countries - Baillie, Vicky L; Moore, David P; Mathunjwa, Azwifarwi; Morailane, Palesa; Simões, Eric A F; Madhi, Shabir A (Journal of clinical microbiology, 2019)
The pathogenesis of human rhinovirus (HRV) during severe respiratory disease remains undefined; thus, we aimed to explore the relationship between the HRV molecular subtyping results obtained during severe and asymptomatic childhood infections. Nasopharyngeal/oropharyngeal swabs from children (1 to 59 months of age) hospitalized with pneumonia and from age-frequency-matched controls were collected between August 2011 and August 2013. Swabs were tested for respiratory pathogens, including HRV, using quantitative real-time PCR assays. HRV-positive samples were sequenced for phylogenetic analysis by targeting the 5' noncoding region (5'NCR). Our data showed that there were no differences in the prevalence of HRV detection among cases and controls (21% versus 20%, 0.693); however, among children 13 to 59 months old, HRV detection was more often case associated (21% versus 16%; 0.009), with the results mainly driven by HRV-C (12% versus 7%; 0.001). Overall, there were no differences in the results of molecular subtyping of the HRV species prevalence among cases (for HRV-A, 48%; for HRV-B, 7%; for HRV-C, 45%) and controls (for HRV-A, 45%; for HRV-B, 10%; for HRV-C, 45% [ 0.496]). Those with pneumonia and HRV-C were older (12.1 versus 9.4 months, 0.033) and more likely to present with wheeze (35% versus 25%, 0.031) than those with HRV-A cases. Thus, the rate of HRV detection was high, with similar degrees of genetic diversity among cases and controls, confounding the interpretation of the presence of HRV in nasopharyngeal samples for attribution of a causal role in the pathogenesis of severe pneumonia in infants. However, among children 13 to 59 months of age, HRV detection, in particular, HRV-C detection, was associated with case status, especially among children with wheezing disease.